A comparative study of pilot-scale bio-trickling filters with counter- and cross-current flow patterns in the treatment of emissions from chemical fibre wastewater treatment plant. (November 2017) - Yang, Zhuhui; Liu, Jia; Cao, Jingyang; Sheng, Dinghe; Cai, Tingjian; Li, Jian
Highlights: Performance of BTFs with counter- and cross-current flow modes was compared in detail. Waste gas containing H2 S, NH3 and mixture of VOCs were purified successfully. Bio-trickling filter was restarted successfully in winter. Influence of flow patterns on microbial diversity was analysed. Abstract: Two pilot-scale bio-trickling filters (BTFs) with counter-current and cross-current flow modes were constructed, and their performance tested, for purifying chemical fibre waste gas containing H2 S, NH3 and VOCs with a maximum gas flow rate of 1008 m 3 h −1 . The counter-current type of BTF presented with superior biodegradation results compared to the cross-current type: it could start up quickly, tolerated high transient shock loadings, and possessed an average contaminant removal efficiency higher than 90% with an empty bed residence time of 59 s. The contaminant removal efficiency could be increased by 50% during winter due to the addition of pipeline insulation. The abundance and diversity from microorganism analysis showed that Dyella, Bacillus, Candidimonas, Pandoraea and Thiomonas were the main bacterial strains forming the community treating the pollutants. The counter-current type BTF functioned most effectively and is proposed for practical application.